Pengaruh Harga, Kualitas Produk, Citra Merek Dan Promosi Terhadap Minat Beli Pada Usaha Minuman Chako Di Madiun - Dyah Ajeng Kartika Sari; Dwi Nila Andriani; Maretha Berlianantiya (Jurnal Ekonomi Manajemen dan Bisnis (JEMB), 2023)
This study aims to: (1) determine the effect of price on purchase intention, (2) determine the effect of product quality on purchase intention, (3) determine the effect of brand image on purchase intention, (4) determine the effect of promotion on purchase intention, (5) determine the effect of price, product quality, brand image, and promotions on buying interest. This research is included in the quantitative research with the type of associative causal research. The population in this study were 178 consumers of Chako drink. The sampling technique used is simple random sampling with a total sample of 123 respondents. In this study, data collection techniques used questionnaires and documentation. The data analysis used was the normality test, multicollinearity test, heteroscedasticity test, linearity test, multiple linear regression analysis, t test, f test, and the coefficient of determination. The results of this study indicate that (1) partially there is a positive and significant influence between price on purchase intention of 18.4% (2) partially there is no positive and significant influence between product quality on purchase intention (3) partially there is a positive influence and significant relationship between brand image and purchase intention by 60.2% (4) partially, there is a positive and significant influence between promotion and purchase intention by 33.1% (5) simultaneously, there is a positive and significant effect between price, product quality, image brand, and promotion on purchase intention of 60.4%, while the rest is influenced by other variables not explained in this study.